Spatiotemporal disparity of breast cancer incidence in Iranian female populations at the district level from 2000 to 2021: Bayesian disease mapping - Shadi Rahimzadeh; James Bentham; Beata Burczynska; Farshad Farzadfar; Mariachiara Di Cesare (PLoS ONE, 2025)
Introduction While trends in breast cancer incidence in Iran are generally monitored at the national level, little is known about subnational variations in these trends. This study aimed to assess the levels and trends (2000–2021) of the relative risk (RR) of breast cancer incidence at the district level in Iran and its relation to key socioeconomic dimensions to understand the full extent of geographical and social inequalities in the country associated with breast cancer morbidity. Methods District-level incidence data by age and sex from the National Cancer Registry System of the Iranian Ministry of Health were used. Related covariates were extracted from the Census and Household Expenditure and Income Survey (HEIS) datasets. The RR of breast cancer incidence was estimated in women above the age of 30 for all 316 districts in Iran from 2000 to 2010 using a Bayesian spatiotemporal model. Finally, predictions were estimated for the period 2011–2021. Results The national RR of breast cancer incidence in Iran increased from 0.21 (95% credible interval (CrI): 0.19, 0.22) in 2000 to 0.66 (0.63, 0.68) in 2010 and 1.23 (1.18, 1.28) in 2021. The RR of breast cancer incidence was highest in Yazd (1.96 [1.63, 2.33]), Shiraz (1.90 [1.72, 2.09]) and Shemiranat (1.90 [1.12, 2.91]) in 2010 and in Tehran (3.99 [3.86, 4.33]), Bushehr (3.89 [3.07, 4.77]) and Abadan (3.67 [2.99, 4.39]) in 2021. In contrast, Savojbolagh, Saravan and Nikshahr had the lowest RRs in both 2010 (0.11 [0.05, 0.20], 0.17 [0.08, 0.30] and 0.20 [0.09, 0.36], respectively) and 2021 (0.19 [0.10, 0.33], 0.34 [0.18, 0.54] and 0.35 [0.17, 0.62], respectively). The RR of breast cancer incidence was 60% greater across districts in the highest YOS quintile (average years of schooling: 3.9) than in those in the lowest YOS quintile (average years of schooling: 2.2; relative index of inequality: 1.6). Conclusions The results show that the RR of breast cancer incidence has increased over time (2000–2021) at the national and subnational levels in Iran. Breast cancer is one of the few diseases with a positive education gradient, with a greater RR of breast cancer incidence among higher-educated women than among lower-educated women. However, this is likely due to better awareness of diagnostic approaches and access to those approaches rather than reflecting patterns in the true incidence of breast cancer. While social inequalities are a major barrier to reducing the prevalence and incidence of breast cancer, it is important to track the progress made at the district level based on the characteristics of specific policies aimed at reducing health inequalities. A scaling-up in the quality of healthcare services, national and subnational policies addressing prevention and treatment, and more specialised training programmes for women’s health are needed.